De novo Gastrinoma: A Case Report - Barbosa,Arsénio (2020)
Gastrinomas are neuroendocrine tumors characterized by gastrin overexpression - 80% are sporadic and 20% are associated with multiple endocrine neoplasia type 1. A 75-year-old male patient, surgically treated at the age of 50 years for gastrinoma, followed on an outpatient basis because of chronic non-bloody diarrhea, was admitted to our hospital because of abdominal pain, watery diarrhea, and nonbiliary vomits. He was hypotensive and showed no response to fluids. Blood cultures were positive for Salmonella, and a diagnosis of septic shock due to Salmonella infection was made. The patients condition improved, but the history of chronic diarrhea was still not explained. To investigate chronic diarrhea, gastrinoma recurrence was considered. Serum gastrin measurement was five times higher than the upper limit of the normal range (536 pg/mL). A positive somatostatin receptor scintigraphy was diagnostic for neuroendocrine tumor. Metastases were excluded. The patient was proposed to curative surgery, and a diagnosis of a well-differentiated neuroendocrine tumor was made.